Impact of School Infrastructure on the Performance of Students at Higher Secondary School - Hina Mahmood; Dr. Jam Muhammad Zafar (Social Science Review Archives, 2025)
This study investigates the influence of infrastructure, including classrooms, labs, libraries, sanitation, and recreation facilities, on both academic and social development (confidence, cooperation, and motivation) of higher secondary students in Rahim Yar Khan, Pakistan, while recognizing the role of school infrastructure as an enabler of inclusive quality education. The Study was designed as a descriptive survey with a concurrent mixed-methods data collection approach (questionnaires, interviews, on-site observations), with 260 sampled higher secondary school principals, teachers, and students from both urban and rural public and private schools. Overall, participants strongly agreed (86–92%) that a safe, clean, well-planned, and accessible infrastructure facilitates teamwork, empathy, and communication skills, and enhances learning outcomes and student confidence in higher secondary education in Pakistan. Notable differences were found between the urban and rural schools in aspects like ICT, co-curricular areas, and inclusive infrastructure. There were also strong positive correlations and good predictive validity between safe, clean, well-maintained facilities and school engagement and achievement levels. The results suggest that infrastructure not only provides support for learning but also significantly molds students’ lives, relationships, and development. The study recommends infrastructure policies that ensure availability, accessibility, maintenance, and integration of digital and inclusive design to support the overarching aims of SDG 4, including quality and equitable education.